1992
DOI: 10.1073/pnas.89.16.7375
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endogenous tumor necrosis factor alpha and transforming growth factor beta during induction of collagen type II arthritis in mice.

Abstract: Both tumor necrosis factor a (TNF-a) and transforming growth factor 13 (TGF-1) are found in synovial fluid from arthritic joints of humans and of rodents with experimental arthritis. The role of endogenously produced TGF-fi and TNF in the pathogenesis of collagen type U-induced arthritis (CIA) in DBA/1 mice was examined by determining the effect of neutralizing monoclonal antibodies to these factors on the course of the disease. Endogenously produced as well as systemically administered TGF-P1 and TNF-a had op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
211
2
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(224 citation statements)
references
References 57 publications
9
211
2
2
Order By: Relevance
“…In vitro, TNF is also less potent Berg et al, 1994;Williams et al, 1992;Piguet et al, 1992;Thorbecke et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, TNF is also less potent Berg et al, 1994;Williams et al, 1992;Piguet et al, 1992;Thorbecke et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To date, it has been shown that systemic administration of TGF-1 to rodents protects against induction of arthritis [12,13] and experimental allergic encephalomyelitis (EAE) [37][38][39][40]. It has also been demonstrated that TGF-2 is as effective as TGF-1 in protecting against EAE [40,41], thus indicating that these TGF-s have similar biological effects in EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of TGF-in the synovium and synovial fluids of RA patients [5][6][7][8][9][10][11]. In rodents, conversely, the action of TGF-or its antagonists administered in vivo in experimental arthritis has been intensively studied [12,13]. However, in the animal arthritis models, little is known concerning both the distribution and the kinetics of the different isoforms of TGF-and its receptors [8].…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory cytokines TNF␣ and IL-1␤ play a crucial role in the pathology of arthritis, driving enhanced production of cytokines, chemokines, and degradative enzymes (12). In vivo studies have shown that neutralizing TNF␣ or IL-1␤ controls chronic inflammation and cartilage degradation, respectively (13)(14)(15). Consistent with this, clinical studies revealed efficacy after blocking of TNF␣ or IL-1␤.…”
mentioning
confidence: 82%